Análise da interação entre ordenamento territorial e biodiversidade: estudo de caso em Villavicencio (Meta, Colômbia) - Ortiz-Moreno, Martha Lucia (Universidade Federal de São Carlos, 2014)
The city of Villavicencio (Meta, Colombia) has three physiognomic units inside their 131.020 ha of extension: mountains, foothills and savannah. The relief, orographic rain and the tropical temperature have a plenty of abiotic resources, which determine the species diversification. However, human influence is a threat to biodiversity due to deforestation, urban growth and disordered mineral exploration. There are currently 11 species of plants and 62 animal species with some degree of endangerment on the city, distributed in the three physiognomic units. Thus, the objective of this research was to make a proposal to insert biodiversity conservation in the municipal Landplane of Villavicencio. The analyses of usage and land cover between 1988 and 2013 show that the city is leaving the agriculture to one side due to the increasing of extensive cattle ranching, which comes to occupy 58.4% of the territory extending from savannah to the mountain region, where both the fragility of the soil and steep slopes are responsible to cause the loss of natural vegetation cover and accelerate erosion process. These cause the siltation of waterways and threaten the headwaters rivers, where it does the abstraction for human consumption. In parallel, the disorganized sprawl of the urban area follows deteriorating the protected wetlands of the municipality and the current occupation of the territory generates a decrease to the green areas, as well as leisure, home services and mobility. In this scenario, it is proposed to increase the permeability of the countryside and the city, by increasing the quality of the forest fragments and their connectivity by expanding the area of RPA in rivers with water abstraction; recovery of forest cover in conservation units and physiognomic unit in mountain and foothills, along with measures to increase effective public space and mobility, prohibiting conflicting uses in areas with higher environmental fragility of the municipality. These proposals would help for the survival of endangered species and the conservation of local environmental services.
Keywords: Conservação; Diversidade biológica; Colômbia; Ecologia da paisagem; Ordenamento territorial; Biodiversity conservation; Colombia; Landscape ecology; Landplaning; Ecosystem services; CIENCIAS BIOLOGICAS::ECOLOGIA